KOMITMEN ORGANISASI MEMODERASI PENGARUH KEADILAN ORGANISASI TERHADAP KINERJA PEGAWAI DINAS KESEHATAN KABUPATEN BOLAANG MONGONDOW SELATAN - Nursia Daeng Salasa; Rahmisyari Rahmisyari; Arifin Arifin (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study examines the moderating role of Organizational Commitment on the effect of Perceived Organizational Justice on Employee Performance at the Health Office of South Bolaang Mongondow Regency. Performance gaps across several community health centers and inconsistent findings in prior studies regarding the direction of organizational commitment's moderating role motivated this study. A quantitative explanatory survey approach was employed involving 162 employees selected from a population of 270 through proportional stratified random sampling. Data were collected using a five-point Likert questionnaire and analyzed with Partial Least Square-Structural Equation Modeling (PLS-SEM) using SmartPLS 3.0. The measurement model results show that all constructs satisfy convergent validity (AVE > 0.50), discriminant validity, and reliability requirements (Cronbach's Alpha and Composite Reliability > 0.90). The structural model results indicate that the interaction between Organizational Commitment and Organizational Justice significantly affects Employee Performance (path coefficient = -0.161; T-statistics = 1.992; P-values = 0.046), although the direction is negative, contrary to the hypothesized strengthening effect. Organizational Commitment is therefore confirmed as a significant moderator, but in an attenuating rather than strengthening direction. This finding is interpreted through Conservation of Resources Theory, in which commitment functions as a psychological resource that buffers employees so that the performance of highly committed employees remains relatively stable despite fluctuations in justice perception. The study contributes theoretical insight into the contextual nature of organizational commitment as a moderator and offers practical implications for designing organizational justice policies that remain sensitive to the composition of employees' commitment dimensions.